Fluticasone/formoterol association favors long-lasting decrease in bronchial reactivity to methacholine and weekly PEF variability. (December 2016) - Cortese, Sara; Gatta, Alessia; Della Valle, Loredana; Mangifesta, Rocco; Di Giampaolo, Luca; Cavallucci, Enrico; Petrarca, Claudia; Paganelli, Roberto; Di Gioacchino, Mario
Inhaled corticosteroids (ICS)/long-acting beta-agonists (LABA) association offers a better asthma control than a higher steroid dose with short-acting beta-agonists as needed. In this study, we evaluated the effect of the association on bronchial hyperreactivity (BHR) and peak expiratory flow (PEF) variability, as such parameters are positively correlated with increased asthma morbidity and exacerbations. Thirty-six adult patients with mild persistent asthma were enrolled. After a 7-day run-in, they were randomly assigned to three therapy regimens for 6 weeks: Group 1, fluticasone 125 μg + formoterol 5 μg in the same device; Group 2, fluticasone 125 μg + formoterol 12 μg as needed; Group 3, fluticasone 250 μg + formoterol 12 μg as needed. We evaluated changes induced in weekly PEF variability (measured during the entire study and 4 weeks of follow-up) and pre- and post-study PD20 methacholine (MCH). Weekly PEF variability decreased in all groups during treatment with the greatest reduction in Group 1, followed by Group 3, and finally Group 2. During the follow-up, no significant changes were detected in Group 1, whereas a trend towards an increased variability was found in Groups 2 and 3. Post-treatment PD20 MCH was significantly higher versus the pre-treatment. The increase observed in Group 1 was significantly higher compared to Groups 2 and 3 and that observed in Group 3 in respect to Group 2. The study proves that both BHR and PEF variability are influenced by ICS. This effect was greater with fluticasone/formoterol association compared to fluticasone alone with formoterol as needed even at higher steroid dose.